A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 1. Revision of the Craspedophorus reflexus group (Coleoptera: Carabidae) - Häckel, Martin (Zootaxa, 2016)
Afrotropical species of the Craspedophorus reflexus group are revised. C. arnosti sp. n. (Central Africa), C. ruvumanus sp. n. (Ruvuma Region, Tanzania) and C. reflexus megamacula ssp. n. (Senegambia) are described. Craspedophorus reflexus group sensu Chaudoir, 1879 is redefined and C. savagei (Hope, 1842) is synonymized with C. reflexus (Fabricius, 1781).